Estimasi Kandungan Degadable Organic Carbon (DOC) pada Sampah Padat Kota yang masuk ke TPA Tanjung Belit di Kota Pasir Pangaraian Provinsi Riau - Faizan Dalilla; Mursyidah Umar; Abrar Ridwan (LPPM ITK, 2017)
Degradable Organic Carbon (DOC) is the important element in forming CH4 in a pile of garbage in the landfill. The calculation of the potential of methane (CH4) in the landfill become the basis for control and management of GHG sourced from landfill. Estimated value of the content of DOC used calculating the weight of municipal solid waste that goes into landfill every day, counting the value of the fraction of the composition and content of dry matter of municipal solid waste by 11 components of garbage (food, paper / cardboard, gardens and parks, nappies, wood, textiles, rubber / leather, plastic, glass, metal and sampahlain etc.), to further multiplied by the fraction of a default value content of DOC in each component of trash and garbage in total. The calculations show that the total weight of waste that goes to landfill every day at 14594.05 kg / day with the largest waste composition in the form of junk food at 49.54%, followed by plastic waste (13.76%) and the smallest is junk metal composition by 1.18%. As for the fraction of the dry matter of the highest value was found in the garbage rubber / leather by 95.31%, followed by wood waste amounted to 78.61% and the smallest value was found in the garbage nappies by 17.43% and 21.23% of food waste. Based on calculations using the value of the total garbage in, the fraction of the composition and the fraction of dry material content and the fraction of DOC.